Sosialisasi Pendidikan Karakter Bagi Generasi Muda di Kelurahan Majapahit Kota Lubuklinggau - Asep Sukenda Egok; Tri Juli Hajani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This community service activity (PKM) aims to determine the benefits of character education socialization activities for the younger generation in Majapahit Village, Lubuklinggau City. The foundation of the main goal is of course that character education remains a priority for the people of Majapahit Village, Lubuklinggau City. The implementation method is a field study using a qualitative design. Data is obtained from interview studies, joint discussions with partners and looking for relevant source references. The results of community service (PKM) are that the people of Lubuklinggau City, especially Majapahit Village, must continue to protect themselves from the influence of the times. Various community activities that can shape character in themselves must continue to be improved. Positive activities such as diligent study for young people, enlivening the Mosque for Muslims, and helping neighbors in difficulty must be done. This is certainly very positive amid the influence of increasingly sophisticated times. The utilization of technology for the younger generation can also be done while still being well controlled. This is because sometimes technology makes children forget to study. The role of parents in providing guidance and control of children is very necessary. In conclusion, as the next generation of the nation, young people must be able to do positive things. In order to make the progress of the times and can be a mainstay for the Indonesian nation in the present and the future.